PENGARUH TEMPERATUR PEMANASAN DAN MEDIA PENDINGINAN PADA PROSES FLAME HARDENING TERHADAP NILAI KEKERASAN PADA BAJA S45C - Machfuroh, Talifatim; Lostari, Aini; Ulum, Miftahul; Pramartaningthyas, Ellys Kumala (Otopro, 2024)
Sprocket is one of the main components in two-wheeled vehicles that transfer the rotary force from the engine to the rear wheels of the motorcycle. Because of this main function, the sprocket wears out faster due to friction between the chain and the sprocket. Therefore, a heat treatment process is needed to improve the mechanical properties of steel to make it more resistant to friction. Based on this background, this research focuses on the effect of temperature and cooling media on the hardness level of the material that receiving heat treatment in the form of flame hardening. The material used is S45C steel. The heat treatment process is carried out on steel with heating temperatures of 750º C and 850º C. After being heated, the steel will be quenched quickly with cooling media in the form of fresh water and turalic oil 48 ISO VG 46. Next, the hardness analysis process is carried out on the test object. From the results of the hardness test, it was found that the highest average hardness value was produced by the test object which underwent a flame hardening process at a temperature of 850 oC with fresh water cooling medium, which was 335.333 HB. Fresh water cooling media tends to produce higher hardness values ​​than turalic oil. This is because the cooling rate of fresh water is faster than oil.